2009
DOI: 10.1002/ar.20907
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Labyrinth Volume and Hearing Abilities in Primates

Abstract: The primate cochlea is a membranous, fluid-filled receptor organ that is specialized for sound detection. Like other parts of the inner ear, the cochlea is contained within the bony labyrinth of the petrous temporal bone. The close anatomical relationship between the bony cochlear labyrinth and the membranous cochlea provides an opportunity to quantify cochlear size using osteological specimens. Although mechanisms of cochlear frequency analysis are well studied, relatively little is known about the functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(28 citation statements)
references
References 49 publications
3
25
0
Order By: Relevance
“…Two recent studies have identified relationships between high-frequency auditory sensitivity and the morphology of the middle ear ossicles [63] and cochlear labyrinth [62,63]. Such findings, in tandem with the present results, suggest that it is plausible to estimate the group sizes of fossil species, including early human ancestors, on the basis of bony ear morphology.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Two recent studies have identified relationships between high-frequency auditory sensitivity and the morphology of the middle ear ossicles [63] and cochlear labyrinth [62,63]. Such findings, in tandem with the present results, suggest that it is plausible to estimate the group sizes of fossil species, including early human ancestors, on the basis of bony ear morphology.…”
Section: Discussionsupporting
confidence: 86%
“…However, this audiometric parameter is limited by the selection of test frequencies and complicated by multiple frequencies having similar thresholds. Accordingly, the 60 dB high-frequency limit is a more practical measure of high-frequency auditory sensitivities; and, in primates, it has been linked to morphological variation within the bony ear [62,63]. We found that average foraging group size explained a significant proportion of the variance associated with 60 dB high-frequency limits (figure 1c), again indicating a strong predictive relationship between social complexity and auditory sensitivity.…”
Section: Resultsmentioning
confidence: 59%
“…Also, of note is the fact that the volume of human eye is ~4 mL, while the volume of cochlea is lesser, ~70-80 μL. 188 Overall, it has been explicitly clear that for both eye and ear, the BDNF has a dose-dependent manner of action. Eventually, it has been shown, that increasing the dose may lead to lack of effectiveness of BDNF neuroprotection, 97 which is possibly due to negative feedback-mediated downregulation of TrkB receptors.…”
mentioning
confidence: 99%
“…Morphological variation of the bony labyrinth across taxa reflects differences in locomotor behavior (Silcox et al 2009;Spoor and Zonneveld 1998;Spoor et al 2007;Walker et al 2008 ) and hearing performance (Coleman and Boyer 2012;Echteler et al 1994;Gleich et al 2005; Kirk and Gosselin-Ildari 2009;West 1985). This structure is thus highly functionally constrained.…”
Section: Have Revived the Hypothesis Of A Special Link Between Adapifmentioning
confidence: 99%
“…Nevertheless, a part of labyrinthine morphological variation may still convey phylogenetic information. Basilar membrane length, the number of spiral turns and cochlear volume relate to low frequency and high frequency sensitivity (Coleman and Boyer 2012;Echteler et al 1994;Kirk and Gosselin-Ildari 2009;West 1985). However, other aspects of the morphology of the cochlea, such as its general geometry and orientation relative to the semi-circular canal system are less likely to reflect hearing performance.…”
Section: Have Revived the Hypothesis Of A Special Link Between Adapifmentioning
confidence: 99%